Micafungin: In-Vitro Activity to Candida and Aspergillus and In-vivo Activity to Candida parapsilosis - Retno Wahyuningsih; Idham Amir; Robiatul Adawiyah (Fakultas Kedokteran Universitas Kristen Indonesia, 2018)
Abstract Candida and Aspergillus, are two important fungi that can cause systemic or invasive mycoses in human. Micafungin is an antifungal agent belongs to echinocandin group with antifungal activity against Candida and Aspergillus. In this study in vitro activity of micafungin against Candida and Aspergillus, and in vivo activity to Candida parapsilosis were presented. A study on the in-vitro activity of micafungin for Candida and Aspergillus was conducted at our laboratory in August-September 2010. We used E-test on Mueller Hinton agar supplemented by 2% glucose and methylen blue as indicator. The strains tested were isolated from blood, bronchial lavage, urine, stool and skin. Candida albicans (ATCC 90028), and Candida parapsilosis (ATCC 22019) were use for quality control of the experiments. The minimum inhibitory concentration (MIC) was read at 24-48 hours after incubation for Candida and 48 hours for Aspergillus. According to MIC the response to micafungin was determined as susceptible (S), susceptible dose dependent (SDD)/ intermediate and resistant (R). Quality control was done in the same method. To support the laboratory work we present an in vivo activity of micafungin as a case report of C. parapsilosis candidemia. All Candida and Aspergillus isolates were within the range of susceptible. From Candida group, C. parapsilosis even though susceptible but shows the highest MIC (0.75 – 1.5). Aspergillus niger showed highest MIC (0.32), and the most frequent causative agent of aspergillosis Aspergillus fumigatus shows low MIC value. The result of quality control is within expected range. Micafungin shows a good antifungal activity to all Candida and Aspergillus Jakarta isolates. In vivo activity of micafungin against C. paraspilosis is inline with the in-vitro result. Key words: Candida, Aspergillus, neonate, candidemia Abstrak Candida dan Aspergillus, adalah dua jamur penting penyebab mikosis invasif atau sistemik pada manusia. Mikafungin diketahui sebagai antijamur golongan echinocandin yang mampu mengeliminasi Candida dan Aspergillus. Dalam penelitian ini kami ingin meneliti kemampuan in vitro mikafungin terhadap Candida dan Aspergillus, serta menyampaikan laporan kasus aktivitas in vivo mikafungin terhadap Candida parapsilosis. Studi untuk mengetahui aktivitas invitro dari mikafungin terhadap Candida dan Aspergillus, dilakukan di laboratorium mikologi departemen Parasitologi FKUI pada bulan Agustus-September 2010. Kami menggunakan E-test pada media agar Mueller Hinton dengan indikator glukosa 2% dan metilen biru. Strain yang kami periksa diisolasi dari darah, cairan bronkial, urin, tinja dan kulit. Sebagai kontrol kualitas uji kepekaan, kami gunakan Candida albicans (ATCC 90028), dan Candida parapsilosis (ATCC 22019). Konsentrasi hambat minimal (KHM) dibaca setelah inkubasi 24-48 jam untuk Candida dan 48 jam untuk Aspergillus. Respons terhadap mikafungin dibaca sebagai susceptible (S), susceptible dose dependent (SDD) / intermediate and resistant (R). Kontrol kualitas uji kepekaan juga dibaca dengan metode yang sama. Guna memperkuat hasil laboratorium, kami laporkan aktivitas in vivo mikafungin terhadap C. parapsilosis pada kasus kandidemia. Seluruh isolat Candida dan Aspergillus sensitif terhadap mikafungin. Dari golongan Candida, C. parapsilosis walaupun masih sensitif namun menunjukkan KHM tertinggi (0,75 - 1,5). Aspergillus niger menunjukkan KHM tertinggi (0,32), dan strain Aspergillus fumigatus sebagai penyebab tersering aspergillosis menunjukkan nilai KHM rendah. Aktivitas Mikafungin bagus sebagai antijamur terhadap semua strain Candida dan Aspergillus di Jakarta. Aktivitas in vivo mikafungin terhadap C. paraspilosis sesuai dengan in-vitro.Kata kunci: Candida, Aspergillus, neonatus, kandidemia